Geomatics and metaverse for lost heritage sites documentation and dissemination: the case study of Palmyra Roman Theatre (Syria) - Anna Forte; Yara Jamil Alkhatib; Gabriele Bitelli; Eva Savina Malinverni; Roberto Pierdicca (Virtual Archaeology Review)
Highlights: